2018
DOI: 10.1159/000491429
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotection by L-Ornithine L-Aspartate in Non-Alcoholic Fatty Liver Disease

Abstract: Background: Non-alcoholic fatty liver disease (NAFLD) is the leading chronic hepatic condition worldwide and new approaches to management and treatment are limited. Summary: L-ornithine L-aspartate (LOLA) has hepatoprotective properties in patients with fatty liver of diverse etiology and results of a multicenter randomized clinical trial reveal that 12 weeks treatment with oral LOLA (6–9 g/d) results in a dose-related reduction in activities of liver enzymes and triglycerides together with significant improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 21 publications
2
33
0
6
Order By: Relevance
“…It was also shown that l ‐arginine improved hepatic microcirculation following ischemia‐reperfusion injury (Uhlmann, Scommotau, Witzigmann, & Spiegel, ). Clinically, a mixture of l ‐ornithine and l ‐aspartate (LOLA) has been shown to have hepatoprotective properties in individuals with fatty liver diseases (Butterworth & Canbay, ). Such hepatoprotection seems to result from the transamination of l ‐ornithine into glutamate (Butterworth & Canbay, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also shown that l ‐arginine improved hepatic microcirculation following ischemia‐reperfusion injury (Uhlmann, Scommotau, Witzigmann, & Spiegel, ). Clinically, a mixture of l ‐ornithine and l ‐aspartate (LOLA) has been shown to have hepatoprotective properties in individuals with fatty liver diseases (Butterworth & Canbay, ). Such hepatoprotection seems to result from the transamination of l ‐ornithine into glutamate (Butterworth & Canbay, ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, a mixture of l-ornithine and l-aspartate (LOLA) has been shown to have hepatoprotective properties in individuals with fatty liver diseases (Butterworth & Canbay, 2019). Such hepatoprotection seems to result from the transamination of l-ornithine into glutamate (Butterworth & Canbay, 2019). Indeed, IV infusion of LOLA in patients with chronic liver disease induced an increase in plasma glutamate, and subsequently restored glutamine levels (Staedt et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the focus of the present review has principally been directed at the potential benefits of LOLA treatment for sarcopenia in cirrhosis. However, there is emerging evidence to support the notion that it may also be beneficial in patients with sarcopenia related to NAFLD/NASH [29]. For example, in a study of 463 patients with fatty liver, 29% of whom were nonalcoholic, treated with oral LOLA for up to 60 days, significant decreases of liver enzymes [30] were noted and in a subsequent RCT, 72 patients treated with oral LOLA for 12 weeks manifested significant dose-related reductions of transaminases together with decreases in triglycerides and improvements in liver/spleen ratios [31].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the potential mechanisms responsible for the hepatoprotective properties of LOLA are few in number and are currently focused on the synthesis of agents derived from the conversion of the constituent amino acids of LOLA to agents with established anti-oxidant properties such as glutathione (GSH) and glutamine [21]. Figures 2a and 2b above and the synthesis of glutamine from glutamate occurs readily in liver and skeletal muscle via the enzyme GS (Figure 2d).…”
Section: Role Of Anti-oxidantsmentioning
confidence: 99%